Infotainment as Text: Deconstruction of Market Libido on Ideological News in the Economy-Politics of Entertainment Media: [Infotainment sebagai Teks: Dekonstruksi Libido Pasar Berita Ideologis dalam Ekonomi-Politik Media Hiburan] - Robby Habiba Abror (UIN Sunan Kalijaga Yogyakarta, 2014)
Television still has been relevant labeled as a magical box that attracted many people. In term of infotainment, television simultaneously contributes the communicative implication to the people. Between January 2013 and January 2014, the Indonesian private television broadcasted at least the average minutes of 30 to 150 per day. The co-modification in infotainment represented the libidinal market of capitalists’ media, ensure the program. Infotainment serves not only as entertainment media, but also as ideological discourse massively entered the public’s domestic sphere. The public becomes closely related to the infotainment. As texts, infotainment is open to various interpretations.[Televisi masih relevan dilabeli sebagai kotak ajaib yang mampu menarik hati khalayak. Melalui salah satu hiburan informasi atau yang sering disebut sebagai infotainment, televisi menyumbang implikasi komunikatif terhadap khalayak secara berkesinambungan. Januari 2013 sampai dengan Januari 2014 televisi swasta setidaknya menayangkan infotainment antara 30 menit sampai dengan 150 menit per hari. Komodifikasi dalam infotainment merepresentasikan libido pasar media kapitalis yang memastikan tetap berjalannya tayangan tersebut. Tidak saja sebagai media hiburan, infotainment menjadi wacana ideologis yang secara masif masuk ke ranah domestik khalayak. Khalayak menjadi dekat dengan selebriti melalui infotainment. Sebagai teks, infotainment terbuka terhadap pelbagai interpretasi.]